Occurrence of LINER galaxies within the galaxy group environment - Coldwell Lloveras, Georgina Vanesa (2017)
We study the properties of a sample of 3967 low-ionization nuclear emission-line region (LINER) galaxies selected from SDSS-DR7, with respect to their proximity to galaxy groups. The host galaxies of LINERs have been analysed and compared with a well-defined control sample of 3841 non-LINER galaxies matched in redshift, luminosity, colour, morphology, age and stellar mass content. We find no difference between LINER and control galaxies in terms of the colour and age of stellar population as a function of the virial mass and distance to the geometric centre of the group. However, we find that LINERs are more likely to populate low-density environments in spite of their morphology, which is typical of high-density regions such as rich galaxy clusters. For rich (poor) galaxy groups, the occurrence of LINERs is approximately two times lower (higher) than the occurrence of matched, non-LINER galaxies. Moreover, LINER hosts do not seem to follow the expected morphology–density relation in groups of high virial mass. The high frequency of LINERs in low-density regions could be due to the combination of a sufficient gas reservoir to power the low-ionization emission and/or enhanced galaxy interaction rates benefiting the gas flow towards their central regions.